Leisure-time. An ethnographic approximation of the codes of occasional sexuality in urbanized youth - Matus, Christian (Última Década, 2020)
The experience of sexuality in entertainment in the youth culture is a phenomenon which has not been very well considered within time to build preventive politics directed to the youth-world in Chile. In their very same scenario of the youth culture, associated with their leisure-time, where the urbanized youth pracitice and develop different experiences of approach to the sexuality articulating particular codes: building intimacy groups, together with time and space, and the approach and aproximation between each other in a festive space. The current article is based on the main results of ethografic investigation by the investigator in the context of «The study of the characteristics of risk and vulnerability of Aids in youth», developed on a national level and considered as an example integrated by youths of middle to lower classes sectors of the cities of Arica, Valparaiso, Santiago and Concepcion.